Religious Character Building In Early Childhood Through Independent Learning - Rika Widya; Hutabarat, Eka Putri Sulistia (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This study aims to determine the planning and implementation carried out by TKIT Baitul Hijrah Binjai City in the formation of religious characters in early childhood through independent learning. This research method uses qualitative research methods with a descriptive approach. The data collection technique is the results of observations made on umar bin khattab class children totaling 15 children, direct interviews with 1 principal, 2 teachers and 2 parents, as well as documentation sourced from the TKIT Baitul Hijrah Kota Binjai education unit curriculum and child development records. Data analysis is carried out through data condensation, data display and conclusion drawing or verification which is arranged into a sentence that contains the findings obtained from the research. The result of this research is that planning for the formation of religious characters through independent learning is carried out by compiling school programs in the form of extracurricular programs and teaching modules that support the formation of religious characters, while the application is carried out using learning methods that are fun for children such as singing, storytelling, role playing and involving parents in learning at home.